Forcing From Lower Thermosphere and Quiet Time Scintillation Longitudinal Dependence. Issue 11 (14th November 2020) - Yizengaw, Endawoke; Groves, Keith
Abstract: The quiet time ionospheric plasma bubbles that occur almost every day become a significant threat for radio frequency (RF) signal degradation that affects communication and navigation systems. We have analyzed multi‐instrument observations to determine the driving mechanism for quiet time bubbles and to answer the longstanding problem, what controls the longitudinal and seasonal dependence of ionospheric irregularity occurrence rate? While VHF scintillation and GNSS ROTI are used to characterize irregularity occurrence, the vertical drifts from JRO and IVM onboard C/NOFS, as well as gravity waves (GWs) amplitudes, extracted SABER temperature profiles, are utilized to identify the potential driving mechanism for the generation of small‐scale plasma density irregularities. We demonstrated that the postsunset vertical drift enhancement may not always be a requirement for the generation of equatorial plasma bubbles. The tropospheric GWs with a vertical wavelength (4 km < λ v < 30 km) can also penetrate to higher altitudes and provide enough seeding to the bottom side ionosphere and elicit density irregularity. This paper, using a one‐to‐one comparison between GWs amplitudes and irregularity occurrence distributions, also demonstrated that the GWs seeding plays a critical role in modulating the longitudinal dependence of equatorial density irregularities. Thus, it is becoming increasingly clear that understanding the forcing from a lower thermosphere is critically essential for the modeling community to predict and forecast the day‐to‐day and longitudinal variabilities of ionospheric irregularities and scintillations. Key Points: Postsunset vertical drift enhancement may not be always a requirement for the generation of equatorial plasma bubbles Upward propagating gravity wave can reach ionosphere and elicit irregularities Longitudinal dependence of density irregularity is controlled by the localized gravity wave seeding